A Study on the Evolution and Localization of the Piano in Thai Traditional Music - Li, Zheng; Phansue, Veera; Jamnongsarn, Surasak (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2026)
This study, set against the backdrop of Thai traditional music culture, examines the historical evolution and localization of the piano in Thai traditional music since its introduction to Thailand in the late nineteenth century. Using historical document analysis, musicological analysis, observation of representative performance practices, and expert interviews, the study explores how the piano gradually transformed from a Western cultural symbol in the royal court into an expressive medium for Thai musical creation, arrangement, performance, and education. The article focuses on analyzing the piano's localization strategies in pitch-system adaptation, melodic and ornament imitation, rhythmic adjustment, ensemble participation, and performance aesthetics. The findings show that the piano in Thailand did not simply replace or assimilate traditional instruments, but was reinterpreted through continuous interaction with Thai musical concepts, especially melody-centered expression, flexible rhythmic treatment, and localized ornamentation. This paper argues that the localization of the piano represents a process of cultural negotiation and creative transformation, demonstrating the openness and creativity of Thai traditional music in the context of modernization and globalization. The study provides a case for understanding how Western instruments can be integrated into non-Western musical traditions while supporting the inheritance and innovation of local musical heritage.